Activation of ClC‐3 chloride channel by 17β‐estradiol relies on the estrogen receptor α expression in breast cancer. Issue 2 (9th June 2017) - Yang, Haifeng; Ma, Lianshun; Wang, Yawei; Zuo, Wanhong; Li, Bingxue; Yang, Yaping; Chen, Yehui; Chen, Lixin; Wang, Liwei; Zhu, Linyan
Abstract : Although extensively studied, the mechanisms by which estrogen promotes breast cancer growth remain to be fully elucidated. Tamoxifen, an antiestrogen agent to treat ERα+ breast cancer, is also a high‐affinity blocker of the chloride channels. In this study, we explored the involvement of the chloride channels in the action of estrogen in breast cancer. We found that 17β‐estradiol (17β‐E2) concentration‐dependently activated the chloride currents in ERα+ breast cancer MCF‐7 cells. Extracellular hypertonic challenge and chloride channel blockers, NPPB and DIDS inhibited the 17β‐E2‐activated chloride currents. Decreased the ClC‐3 protein expression caused the depletion of the 17β‐E2‐activated chloride currents. 17β‐E2‐activated chloride currents which relied on the ERα expression were demonstrated by the following evidences. Firstly, 17β‐E2‐activated chloride currents could not be observed in ERα‐ breast cancer MDA‐MB‐231 cells. Secondly, ER antagonists, tamoxifen and ICI 182, 780, and downregulation of ERα expression inhibited or abolished the 17β‐E2‐activated chloride currents. Thirdly, ERα expression was induced in MDA‐MB‐231 cells by ESR1 gene transfection, and then 17β‐E2‐activated chloride currents could be observed. In MCF‐7 cells, ERα and ClC‐3 mainly located in nucleus and translocated to cell plasma and membrane with respect to co‐localization following treatment of 17β‐E2. Downregulation of ERα expression could decrease the expression of ClC‐3 protein. Conversely, downregulation of ClC‐3 expression did not influence the ERα expression. Taken together, our findings demonstrated that ClC‐3 is a potential target of 17β‐E2 and is modulated by the ERα in breast cancer cell. Pharmacological modulation of ClC‐3 may provide a deep understanding in antiestrogen treatment of breast cancer patients.